Climate Change in the Context of the Energy Reform in Mexico - Gutiérrez Nájera, Raquel (Derecho & Sociedad, 2014)
The author analyzes the Mexico’s energetic reform during the sexennial of 2013 to 2018. A historic study refers that Mexican energy matrix was based on fossil sources of energy as crude oil and natural gas. This represents nearly 90% of primary energy’s total production while the profit of non-fossil energy represents only 8% until 2012.Then, during the period of 2007-2012, the majority of the programmatic and normative instruments about climate change were generated. From 2013 to 2018, said the author, a national structural reform has been discussed. Thisamend includes Mexico’s energetic reform that proposes the «fossilization» of Mexican economy. This «fossilization» of the economy will favor the green growth and will constitutes itself as a barrier for Mexico’s fulfillment of international commitments assumed aboutclimate change, as well as its transition to a low carbon economy.